Investigation of weld zone and fracture surface of friction stir lap welded 5052 aluminum alloy and 304 stainless steel joints - Chitturi, V. (MDPI AG, 2020)
Dissimilar material joining of aluminum and steel in the present scenario is an important criterion in the manufacturing industry, especially because of their low weight and technical performance. In the present investigation, AA5052 and SS304 are friction stir welded in lap configuration with different tilt angles, welding speed, pin depth, and tool rotational speed, with aluminum as the top plate. A maximum of 3.16 kN shear strength was achieved at 2.5â¦ tilt angle when the penetration depth was 4.3 mm. The shear strength samples were studied for fracture analysis and it was found that fracture of the samples mainly occurred on the aluminum side and the fracture demonstrated both brittle and ductile failure, consisting of quasi-cleavage, trans-granular, and intergranular fracture areas. Field emission scanning electron microscope images at the interfacial region of the weld show that different intermetallic compounds were formed at various zones of the joint with respect to the change in process parameters. It was observed from energy dispersive spectroscopy that Al-rich intermetallic compounds were formed at the interfacial region of the welded samples. Amongst the process parameters, change in the tilt angle affected the weld zone significantly. The thickness of the intermetallic compound (IMC) layer formed with 800 and 1000 rpm at 2.5â¦ tilt angle was between 2.5 and 3 Âµm, which resulted in achieving better joint strength. AlFe, AlFe3, Al13Fe4, and Al5Fe2 were the different intermetallic compounds detected using X-ray diffraction with different process parameters. The hardness of the samples ranged between (300 and 630) HV, which further supports the formation of AlFe and AlFe3 intermetallic compounds. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.